Edukasi Kasus Kegawatdaruratan Dental bagi Komunitas Wisatawan di Bali - Rejeki, Putri; Kristanto, Riki; Nyoman Ari Susanti , Desak; Ayustina Prasetya, Mia; Aditya Handoko, Steffano; Dananjaya Agung, A.A.G. (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
Dental Tourism is a new form of tourism where dental treatment is combined with tours, and several medical travel agencies provide specialized services. Dental tourism itself is an important segment of the growing trend of medical tourism worldwide. Tours and travel agencies consist of tour guides. The main responsibility of tour guides is to accompany tourists and, more importantly, they have a role in creating the quality of tourism. The quality of tourism itself is not only based on the segments of a tour, but also on the insights of tour guides in assisting tourists in various aspects, including medical and dental tourism. The results of the counseling show paired t-test analysis with a p-value of 0.12, which is greater than 0.05, meaning there is a significant relationship between before and after the counseling. In this case, it illustrates the benefits of counseling that provide additional positive value to the knowledge of a tour guide related to dental emergencies.